2018
DOI: 10.3389/fonc.2018.00364
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Glycans in Hematological Malignancies

Abstract: The three types of blood cells (red blood cells for carrying oxygen, white blood cells for immune protection, and platelets for wound clotting) arise from hematopoietic stem/progenitor cells in the adult bone marrow, and function in physiological regulation and communication with local microenvironments to maintain systemic homeostasis. Hematological malignancies are relatively uncommon malignant disorders derived from the two major blood cell lineages: myeloid (leukemia) and lymphoid (lymphoma). Malignant clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 141 publications
2
22
0
Order By: Relevance
“…As a consequence, tumor cells express aberrant N-glycans, which have been shown to be associated with malignancy and poor prognosis. The correlation between tumor progression and the terminal modification of N-glycans has long been an extensive focus of basic and clinical research studies in glycobiology and have been sophisticatedly reviewed elsewhere [6,7,8,9,10,11,12,13,14,15,16]. In contrast, the association of OST with tumor progression has only recently been explored.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, tumor cells express aberrant N-glycans, which have been shown to be associated with malignancy and poor prognosis. The correlation between tumor progression and the terminal modification of N-glycans has long been an extensive focus of basic and clinical research studies in glycobiology and have been sophisticatedly reviewed elsewhere [6,7,8,9,10,11,12,13,14,15,16]. In contrast, the association of OST with tumor progression has only recently been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, among the top 10% genes exhibiting the most significant transcript abundance shift (Table S1), we found the gene B4GALT1. Notably, B4GALT1 protein has been previously associated with multi-drug-resistant cell phenotype in human leukemia [52] and other haematological malignancies [53,54]. On the other side, genes significantly downregulated were associated with MYC and E2F target genes (Figure S2).…”
Section: Resultsmentioning
confidence: 89%
“…More recently, it was reported that small RNAs which are modified with N-glycans are displayed on the surface of living cells [227]. Many malignancies are characterized by abnormal glycosylation, which is commonly associated with the oncogenesis and cancer progression [224][225][226][228][229][230][231][232][233][234][235][236][237][238]. Furthermore, persistent non-malignant inflammatory conditions cause continual upregulation of enzymes that promote numerous molecular changes, including glycosylation as well [228][229][230][231][232][233][234][235][236][237].…”
Section: Applications Of Immunoaffinity Capillary Electrophoresis the Importance Of Detecting Molecular Modifications Of Proteins During mentioning
confidence: 99%